Performance analysis of composite laminates wing skin with the aid of fluid structure interaction of aerodynamic loading-structural analysis - Basri, Ernnie Illyani; Basri, Adi Azriff; Balakrishnan, Sarveshwaaran; Haji Hameed Sultan, Mohammed Thariq; Ahmad, Kamarul Arifin (Taylor and Francis Group, 2022)
Advances in today’s technology have led to the use of composite materials with their advantages of significant high strength with lightweight structure in aircraft design worldwide. With the aid of simulation, ANSYS, two main common problems in designing the aircraft composite wing, which is the aerodynamic loading on the wing and composite modeling; whereby both can be coupled to solve the aforementioned problems. The paper addresses with the use of fluid Structure Interaction (FSI) simulation and developed a standard numerical approach by integrating the aerodynamic loading from fluid domain with Finite Element (FE) analysis from structural domain in the application of hybrid composite laminates of aircraft wing structure. In this study, the Computational Fluid Dynamics (CFD) is conducted on the selected wing model of Selig 1223 in order to obtain the pressure loading from fluid domain before transferring it as an input to FE composite of structural domain. The FSI simulation was performed for two parametric conditions, namely Composite Wing Skin without Honeycomb (CWS) and Composite Wing skin with Honeycomb (CWSwH). From the result, CWSwH has lower total deformation with 3.06% percentage difference compared to CWS. However, the shear stress and strain values of CWSwH showed higher value than those of CWS due to the effect of the elasticity of honeycomb core. Therefore, the numerical approach of FSI with the application composite material has proven to be feasible and significant of current research on the behavior of fluid flow and structural for the wing skin, which replicates the real conditions of the aircraft wing during take-off or cruise.